A variable neighbourhood search algorithm with compound neighbourhoods for VRPTW - Chen, Binhui; Qu, Rong; Bai, Ruibin; Ishibuchi, Hisao (2016)
The Vehicle Routing Problem with Time Windows (VRPTW) consists of constructing least cost routes from a depot to a set of geographically scattered service points and back to the depot, satisfying service time interval and capacity constraints. A Variable Neighbourhood Search algorithm with Compound Neighbourhoods is proposed to solve VRPTW in this paper. A number of independent neighbourhood operators are composed into compound neighbourhood operators in a new way, to explore wider search area concerning two objectives (to minimize the number of vehicles and the total travel distance) simultaneously. Promising results are obtained on benchmark datasets